2009
DOI: 10.1002/macp.200800622
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chitosan Surfactants

Abstract: Chitosan surfactants were prepared in a three‐step reaction starting with glycol chitosan (GC) and chitosan oligosaccharides (COS). In the case of GC, water‐insoluble products were obtained, the functionalisation of which were proven via IR spectroscopy. Starting with COS, a broad variety of products with different ratios of ionic and hydrophobic side chains were prepared and characterised by NMR and partially by IR spectroscopy. Thermogravimetric analysis showed that the thermal stability of functionalised CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The photoinitiators used in this study, 2-hydroxy-2-methylpheny-propane-1-one (1173), 2,4,6-trimethyl benzoyldiphenyl phosphine oxide (TPO), benzophenone (BP) and ethyl-4-dimethylaminobenzoate (EDAB), were donated by Runtec Chemistry (Changzhou, Jiangsu, P. R. China). [17] Trimethylolpropane (67 g, 0.5 mol), dimethyl carbonate (135 g, 1.5 mol) and DABCO (0.56 g, 5 mmol) were heated at 75 • C for 16 h. Then methanol and excess dimethyl carbonate were removed by distillation. EDO was obtained in quantitative yield and was used without further purification for the next step.…”
Section: Methodsmentioning
confidence: 99%
“…The photoinitiators used in this study, 2-hydroxy-2-methylpheny-propane-1-one (1173), 2,4,6-trimethyl benzoyldiphenyl phosphine oxide (TPO), benzophenone (BP) and ethyl-4-dimethylaminobenzoate (EDAB), were donated by Runtec Chemistry (Changzhou, Jiangsu, P. R. China). [17] Trimethylolpropane (67 g, 0.5 mol), dimethyl carbonate (135 g, 1.5 mol) and DABCO (0.56 g, 5 mmol) were heated at 75 • C for 16 h. Then methanol and excess dimethyl carbonate were removed by distillation. EDO was obtained in quantitative yield and was used without further purification for the next step.…”
Section: Methodsmentioning
confidence: 99%
“…Because of differences in reactivities between the two carbonate functional groups towards amino nucleophiles, it is possible to perform these reactions selectively. Recently, the reactivity of difunctional carbonate couplers with different leaving groups (LGs) was reported, and their coupling ability towards amino acid methyl esters and glucosamine was determined; [5] LGs were para-nitrophenol, phenol, imidazole and acetone oxime. It was shown that the substitution reaction is much faster than the addition reaction; no conversion of the five-membered ring carbonate was observed below 70 8C.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, an asymmetric A,A 0 -carbonate coupler [(2-oxo-1,3-dioxolan-4-yl)methylphenyl carbonate, A1] was developed in our group to selectively combine monodisperse functional amine building blocks and polyamines within a single molecule. [2][3][4][5][6][7][8][9][10] At low temperatures (0-25 8C) the phenyl carbonate of the bifunctional coupler was first substituted selectively with hydrophilic, hydrophobic, or ionic primary amines to result in functionalized couplers, or with polyamines to result in a polyamine-coupler adduct. Then, at higher temperatures (60-80 8C) the functionalized couplers are reacted with a polyamine, respectively, the polyamine-coupler adducts are reacted with amine building blocks to produce multifunctional polymers.…”
Section: Introductionmentioning
confidence: 99%
“…During these reactions the cyclic carbonate ring is opened and a urethane group with an adjacent hydroxyl group is formed. Based on coupler A1, several functionalized couplers were prepared and successfully used for the modification of branched polyethyleneimine (B-PEI), [2][3][4][5][6][7] chitosan, [9] and aminofunctional polysiloxane. [10] Polymers bearing amine groups, the so-called polyamines, are an interesting class of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation